Pollen and spores records of lake sediments from the Eifel, Germany - Sirocko, Frank; Albert, Johannes; Britzius, Sarah; Dreher, Frank; Martínez-García, Alfredo; Dosseto, Anthony; Burger, Joachim; Terberger, Thomas; Haug, Gerald H (PANGAEA, 2025)
In order to reconstruct the presence of Megafauna in relation to vegetation cover in Central Europe, a total of 250 pollen samples and 203 samples for spores of the coprophilous fungi Sporormiella and Sordaria were analyzed. The results are accompanied by measurements of δ7Li and n-alkanes. Samples derive from composite drill cores from Holzmaar and Auel infilled maar and cover the last 60,000 years. This work is part of the ELSA project.
Keywords: Central Europe; lake sediments; Marine Isotope Stage 3; megafauna